Pengaruh Banyaknya Informasi, Kualitas Informasi, Kredibilitas Sumber e-WOM terhadap Niat Membeli Produk Fashion Online pada Generasi Milenial - Servasia Petra Rosari Yusandani; Minta Istono (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2021)
Abstract.This study aims to determine the correlation between perceptions of electronic- word-of-mouth (e-WOM) with the intention of buying online fashion products among the millennial generation. The hypothesis of the proposed research is the positive and significant correlation between the variables of perceptions of e-WOM with the intention of buying online fashion products among the millennial generation. The subjects in this study were 684 people born in 1980-2000 who has no prior access or purchase of fashion products online and read the reviews or reviews online about fashion products. The data was collected by distributing a questionnaire study that contains scaled perceptions of e-WOM (21 items, 0.885) and purchase intention scale of online fashion products (4 items, ). The test results showed the assumption that the data are not eligible for normality but were qualified for linearity. The data analysis was performed using Spearman's rho method. Test results analysis shows that the variable perceptions of e-WOM positively correlated with the intention of buying online fashion products. Both of these variables have a correlation coefficient of r = 0.227 and the value of significance p = 0.000. Each dimension in the variable perceptions of e-WOM positively correlated with the intention of buying online fashion products. Dimensions credibility of e-WOM has a correlation coefficient of r = 0.221 and the value of significance (p = 0.000), the dimensions of the quality of e-WOM has a correlation coefficient of r = 0.239 and the value of significance (p = 0.000), and the dimensions of the quantity of e-WOM has a value the correlation coefficient r = 0.123 and the value of significance (p = 0.000).